BISTABILITY OF ELLIPTICALLY POLARIZED OSCILLATION IN A MOLECULAR-BEAM MASER OPERATED WITH A DISK RESONATOR - Laine, D; Yassin, G (1981)
Elliptical oscillation in a molecular beam maser operated with a disc resonator is shown to exhibit a polarization bistability. The various experimental conditions under which the phenomenon arises are discussed and an interpretation given in terms of anisotropic properties of the resonator and the state selected molecular beam. © 1981.